2017
DOI: 10.18632/oncotarget.15329
|View full text |Cite
|
Sign up to set email alerts
|

S100A7 promotes the migration, invasion and metastasis of human cervical cancer cells through epithelial-mesenchymal transition

Abstract: S100A7 is an EF-hand calcium-binding protein that has been suggested to be implicated in cell proliferation, migration, invasion and tumor metastasis. However, its role in cervical cancer has not yet been fully clarified. The present study used immunohistochemistry analysis of S100A7 in clinical specimens of cervical cancer to show that S100A7 expression was significantly upregulated in cervical cancer tissues compared with normal cervical tissues and S100A7 expression in high grade cervical intraepithelial ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…The phenomenon known as epithelial-mesenchymal transition (EMT) promotes invasion and metastasis in many cancers [29][30][31], and we hypothesized that S1PR1 might be involved in EMT of GC cells. We treated MGC-803 cells with 10 ng/ml TGF-β1 for 24 hours.…”
Section: S1pr1 Expression Is Elevated In a Tgf-β1 Induced Emt Modelmentioning
confidence: 99%
“…The phenomenon known as epithelial-mesenchymal transition (EMT) promotes invasion and metastasis in many cancers [29][30][31], and we hypothesized that S1PR1 might be involved in EMT of GC cells. We treated MGC-803 cells with 10 ng/ml TGF-β1 for 24 hours.…”
Section: S1pr1 Expression Is Elevated In a Tgf-β1 Induced Emt Modelmentioning
confidence: 99%
“…Limited studies have been done to evaluate the effect of ASCs on cervical cancer. However, one study by Tian et al found that S100A7, described above for its role in breast cancer proliferation and metastasis, has also been shown to enhance cell migration, invasion, metastasis and the epithelial to mesenchymal transition of cervical cancer . ASC secretion of two pro‐inflammatory cytokines IL‐8 and IL‐6, described below, was increased when cocultured with bladder cancer cells .…”
Section: Ascs In Cancermentioning
confidence: 99%
“…by regulating cell proliferation, metastasis, migration, invasion, apoptosis and angiogenesis (17)(18)(19). Mechanistically, several signaling pathways have been demonstrated to have a correlation with psoriasin, including Hippo, receptor for advanced glycation endproducts (RAGE), extracellular signal-regulated kinase (ERK), β-catenin and nuclear factor (NF)-κB pathways.…”
Section: Psoriasin Overexpression Confers Drug Resistance To Cisplatimentioning
confidence: 99%
“…Similarly, psoriasin promotes cell survival by binding to c-Jun activation domain-binding protein1 and enhancing the phosphorylation of NF-κB and protein kinase B in breast cancer (20). Another study demonstrated that psoriasin binds to RAGE and activates ERK signaling to increase migration and invasion in cervical cancer (18). However, the role of psoriasin in GC and its underlying mechanisms remain unclear.…”
Section: Psoriasin Overexpression Confers Drug Resistance To Cisplatimentioning
confidence: 99%
See 1 more Smart Citation